(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
The International Docking System Standard (IDSS) is a technical interface that enables different spacecraft to connect safely in orbit. Under the United States led Artemis Accords, 52 partner nations are required to adopt this standard to ensure mission safety and interoperability. However, scholars disagree about the political implications of this technical requirement. This study addresses the following research question: How does the IDSS standard redefine international power dynamics in the Artemis led lunar exploration? Drawing on the theoretical frameworks of Stewart and Dittmer (2023) and Morin and Tepper (2023), the research analyzes official documents, academic literature, and historical cases such as the Apollo Soyuz Test Project. The findings reveal a fundamental paradox: The IDSS simultaneously functions as a “material vernacular” that facilitates international cooperation and as a “chokepoint effect” that creates a United States led technological hierarchy. Shared docking standards enable states to collaborate, even during terrestrial political conflicts. At the same time, they bind partner nations to American engineering norms, restrict their strategic autonomy, and marginalize rival powers such as China. The paper concludes that technical standards are never neutral; they embed structural power and reshape international relations. These findings are particularly important for emerging space nations that must balance the benefits of interoperability against the risks of long term dependency. As the Moon becomes a new arena for great power competition, understanding who writes the technical rules is as critical as understanding who builds the rockets.